1985
DOI: 10.1111/j.1464-5491.1985.tb00640.x
|View full text |Cite
|
Sign up to set email alerts
|

A Microbiological Study of Diabetic Foot Lesions

Abstract: The bacterial nature of infected foot lesions presenting to a diabetic unit during the course of twelve months was studied. Fifty-six swabs were obtained from 25 patients. Swabs were processed within ten minutes of being collected. An average of 3.3 organisms per swab were isolated, Staphylococcus aureus was the most common bacterial species isolated, while anaerobic bacteria comprised 10% of the isolates. Sensitivity testing of the isolates against commonly used antibiotics showed that the antimicrobial regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Severe and moderate DFIs are usually polymicrobial in nature, whereas mild DFI are mostly monomicrobial [2,4,[9][10][11]. In our study, 20.2% of the patients had mild infection.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Severe and moderate DFIs are usually polymicrobial in nature, whereas mild DFI are mostly monomicrobial [2,4,[9][10][11]. In our study, 20.2% of the patients had mild infection.…”
Section: Discussionmentioning
confidence: 86%
“…First culture results were monomicrobial in 78% of cases with mild DFI, while they were polymicrobial in 73% of cases with moderate to severe infections. Studies from western countries show that Gram-positive aerobes are the predominant organisms isolated from DFI [4][5][6][7][8][9][10][11]. In contrast, two recent Indian studies have shown a preponderance of Gram-negative aerobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often in association with lack of sensation, stiffened arteries, compromised host immune response, and recurrence of ulcers especially harbored by multidrug-resistant organisms places diabetic foot patients at higher risk of non-healing ulcers. Earlier studies have shown that most diabetic foot infections are polymicrobial with a predominance of Gram-positive cocci especially S. aureus , and Streptococci (Sapico et al, 1984; Jones et al, 1985). However, recent studies indicate the dominance of Gram-negative pathogens in the monomicrobial state, particularly members of family Enterobacteriace and Pseudomonas (Tiwari et al, 2011; Turhan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic Streptococci may be isolated in one‐third of cases and usually are found in a polymicrobial infection. Non‐limb‐threatening infections average about 2.1 microbial species per ulcer; however, many are monomicrobial 22–24 …”
Section: Microbiologymentioning
confidence: 99%